New concepts in accommodation and presbyopia - Santos-Neto,Edson dos (2011)
The authors conducted a review of classical and conflicting theories of accommodation and presbyopia. They make a critical comparison with the findings of magnetic resonance imaging (MRI) that have been developed in recent decades. Based on these studies, formulates a new approach on the subject, shifting the focus of the discussion of the lens to the posterior pole of the eye.